IMPLEMENTASI PAHLAWAN EKONOMI KREATIF UNTUK MENINGKATKAN PEMASARAN PRODUK UMKM DI KOTA MALANG - Mar’atul Fahimah; Ospa Pea Yuanita Meishanti (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Creative economy growth in Indonesia can contribute to national grossdomestic product (GDP). The Creative Economy Agency established 16 sub-sectors thatwere developed. Current conditions are still many obstacles found. One of the obstaclesfaced in marketing creative economy products. This study purposes to determine theunderstanding of creative economic actors about electronic commerce (E-Commerce)and creative economic development strategies to improve product marketing. Case studyor qualitative research research method. In this case, the researchers in this study acts asa data collection seeker which is then analyzed. Researchers present directly in order tocollect data, meet directly the parties who might information or data. The results of thisresearch: 1) the creative economy heroes program can improve understanding of ecommerce, 2) the government encourages the use of e-commerce as the right solution in marketing creative economy SMEs products.